Schnitzler's syndrome: diagnosis, treatment, and follow‐up. Issue 5 (9th March 2013) - Simon, A.; Asli, B.; Braun‐Falco, M.; De, H.; Fermand, J.‐P.; Grattan, C.; Krause, K.; Lachmann, H.; Lenormand, C.; Martinez‐Taboada, V.; Maurer, M.; Peters, M.; et al.
Abstract Schnitzler's syndrome is characterized by recurrent urticarial rash and monoclonal gammopathy, associated with clinical and biological signs of inflammation and a long‐term risk of AA amyloidosis and overt lymphoproliferation. An extensive literature review was performed, and the following questions were addressed during an expert meeting: In whom should Schnitzler's syndrome be suspected? How should the diagnosis of Schnitzler's syndrome be established? How should a patient with Schnitzler's syndrome be treated? How should a patient with Schnitzler's syndrome be followed up?. A diagnosis of Schnitzler's syndrome is considered definite in any patient with two obligate criteria: a recurrent urticarial rash and a monoclonal IgM gammopathy, and two of the following minor criteria: recurrent fever, objective signs of abnormal bone remodeling, elevated CRP level or leukocytosis, and a neutrophilic infiltrate on skin biopsy. It is considered probable, if only 1 minor criterion is present. In patients with monoclonal IgG gammopathies, diagnosis is definite if three minor criteria are present and possible if two are present. First‐line treatment in patients with significant alteration of quality of life or persistent elevation of markers of inflammation should be anakinra. Follow‐up should include clinical evaluation, CBC and CRP every 3 months and MGUS as usually recommended.